Colour and The Argument from Illusion - Yetman, Cameron (Stance: an international undergraduate philosophy journal, 2019)
For A. J. Ayer, the occurrence of delusions confutes the notion that we perceive the world directly. He argues instead that perceptions are caused by immaterial “sense data” which somehow represent the properties of material things to us in our experiences. J. L. Austin systematically rejects Ayer’s claims, arguing that the occurrence of delusions does not preclude the possibility of direct perception, and that, indeed, our normal perception is direct. I challenge both philosophers’ ideas by examining how they deal with the phenomenon of colour.